2020
DOI: 10.20473/cdj.v10i2.2020.48-50
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Mangosteen (Garcinia mangostana L.) Flavonoids against Streptococcus mutans Bacteria

Abstract: Background: Dental caries is one of the most common infectious diseases and often occurs in the community caused by bacteria. Attached bacteria in the tooth surface for a long time will form a biofilm and will lead to demineralization characterized by damage in the structure of the tooth enamel. The bacteria that cause dental caries and can form biofilms is Streptococcus mutans. The bacteria inside biofilms are more resistant to antibacterial agents. Flavonoids in mangosteen pericarp extract can be a cleaner a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[ 24 ] Among these, α-MG shows promising results with antimicrobial activity both in vitro and in vivo . [ 8 9 10 ] The present study demonstrated that the α-MG soluble film possesses antimicrobial, antibiofilm, and anti-inflammatory activities without cytotoxic effects. Thus, this film could be developed as a novel product for the prevention of common oral diseases such as dental caries, periodontal disease, and oral candidiasis, or as an adjunctive treatment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…[ 24 ] Among these, α-MG shows promising results with antimicrobial activity both in vitro and in vivo . [ 8 9 10 ] The present study demonstrated that the α-MG soluble film possesses antimicrobial, antibiofilm, and anti-inflammatory activities without cytotoxic effects. Thus, this film could be developed as a novel product for the prevention of common oral diseases such as dental caries, periodontal disease, and oral candidiasis, or as an adjunctive treatment.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study reported that oral spray containing α-MG showed antifungal activity against C. albicans with MIC and MFC of 23.4 µg/mL, and it also had some antibacterial activity against S. mutans with MIC and MBC of 31.2 and 62.5 µg/mL, respectively. [ 10 ] Another study by Juntavee et al [ 9 ] reported bactericidal activity against S. mutans of mangosteen extract with an MIC of 0.25 mg/mL. The time-kill kinetics revealed that 1 mg/mL of the extract reduced S. mutans by 50% and dropped to zero within 5 s and 60 s, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation